ChemInform Abstract: Addition of Organometallic Reagents to Chiral N‐Methoxylactams: Enantioselective Syntheses of Pyrrolidines and Piperidines. Issue 22 (3rd June 2014) - Jaekel, Mascha; Qu, Jianping; Schnitzer, Tobias; Helmchen, Guenter
Abstract Application of this method is demonstrated in the total syntheses of two natural alkaloids, i.e.